Tecnetium-99m as alternative to produce somatostatin-labeled derivatives: comparative biodistribution evaluation with 111In-DTPA-octreotide - Melo, I. B.; Ueda, L. T.; Araujo, E. B.; Muramoto, E.; Barboz, M. F.; Mengatti, J.; Buchpiguel, C. A.; Silva, C. P. G. (Cellular and Molecular Biology, 2010)
Synthetic somatostatin (SST) analogues have been used in the preparation of receptor-specific radiopharmaceuticals for diagnostic and therapy of neuroendocrine tumors. This work studied the labeling conditions with 99mTc and biological distribution in Swiss mice of two SST analogs (HYNIC-Tyr3-Octreotide and HYNIC-Tyr3-Octreotate) and compared the biodistribution pattern with 111In-DTPA-Octreotide. Biological distribution studies were performed after injection of radiopharmaceuticals on Swiss mice. Labeling procedures resulted on high radiochemical yield for all three preparations and the labeled products presented high in vitro stability. Biological distribution studies evidenced similar general biodistribution of 99mTc-labeled peptides when compared with indium-labeled peptide with fast blood clearance and elimination by urinary tract. Kidneys uptake of 99mTc-HYNIC-TATE are similar to 111In-DTPA-Octreotide, and both are significantly higher than 99mTc-HYNIC-OCT. All labeled peptides presented similar uptake on liver, but the retention in time at intestines, particularly at large intestine, was more expressive for 111In-labeled peptide. The %ID of 99mTc-HYNIC-OCT and 99mTc-HYNIC-TATE in organs with high density of SST receptors like pancreas and adrenals were significant and similar to obtained for 111In-DTPA-Octreotide, confirming the affinity of these radiopharmaceuticals for the receptors.